Simultaneous determination of 42 pharmaceuticals in seafood samples by solvent extraction coupled to liquid chromatography–tandem mass spectrometry. (30th August 2020) - Miossec, Carole; Mille, Tiphaine; Lanceleur, Laurent; Monperrus, Mathilde
Highlights: A multi-residue determination of 42 pharmaceuticals in seafood is presented. A very simple methanol extraction combined with an LC–MS/MS analysis is proposed. Validation data including hake, red mullet, sole and shrimp matrices are provided. Commercial seafood muscles from the Bay of Biscay (France) have been analysed. 4 compounds were detected, Caffeine exhibited the highest concentration. Abstract: An efficient and sensitive analytical method based on liquid chromatography–tandem mass spectrometry (LC–MS/MS) has been developed and validated for the simultaneous determination of 42 pharmaceuticals belonging to different therapeutic classes (i.e. antibiotics, analgesics, anti-inflammatories, cardiovascular agents, anxiolytics and human indicators) in seafood samples. The very simple sample preparation included analytes extraction with acidified methanol, concentration by evaporation and filtration of the final extract prior to LC–MS/MS analysis. Analytical performances were evaluated in muscles of four commercial species (hake, red mullet, sole and shrimp) and showed good recoveries at two spiked concentration levels, with relative standard deviations below 45%. Limits of quantification ranged from 0.1 to 40.2 ng/g. This procedure has been successfully applied to the determination of the target analytes in seafood collected from the Bay of Biscay (Southern France) and 4 of these 42 pharmaceuticals were detected at low ng/g levels, suggesting a very limited contamination.